THE INFLUENCE OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN PT. AGRO GEMILANG SURYA PALEMBANG - Sukaria Darmawan; Yuli Anita; M Ilham Pratama (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
The effect of work discipline on employee performance at PT. Agro Gemilang Surya Palembang. This study aims to determine and analyze employee performance. In connection with this how employees can work as well as possible and employees have high work discipline in completing work with discipline. Thus, on this matter, this study aims to show the significance of the influence of work discipline on employee performance. In analyzing the data used descriptive analysis which contains the distribution of items from each variable, then simple linear regression analysis and hypothesis testing. Based on the results of observation and testing of research variables, it can be concluded that work motivation has a positive effect on employee performance at PT. The R2 value of 0.574 means that the percentage contribution of Discipline to performance is 025.1%, while the rest is influenced by other variables not included in this model. Work discipline variable (X) obtained a t value of 6.970 while t table obtained a value of 0.606. Because t count (1.672) > t table (0.606), work discipline partially affects performance.